(untitled) (Biological Sciences - PJSIR, 2002)
A bimolecular reaction between potassium iodide and potassium bromate in presence of sodium nitrate was studied at various ionic strengths (µ) and temperatures. The results showed that the rate constants (k) increased with the increase in ionic strength of the medium. The values of energy of activation (E) and activation parameters such as change in enthalpy of activation (Af-I#), change in entropy of activation (1".S#) and change in free energy of activation (l".QII) were evaluated as a function of ionic strength of the medium.